Estudo do reconhecimento de emoções em adultos com dor lombar crônica inespecífica - Isabella Campolina Mourão Mendonça (2023)
Pain is an unpleasant and entirely subjective emotional experience. The experience of pain is an individual one, in which each person learns and utilizes the concept of pain based on their life experiences. Low back pain (LBP) is very common in the population and occurs in 70%-80% of adults at some point in their lives. LBP is localized below the rib margin and above the upper gluteal line, and it can manifest with or without pain related to the lower limb. Pain and emotions play crucial roles in survival, acting as protective mechanisms against dangers. While distinct concepts, pain and emotions share several characteristics and can produce similar behavioral, physiological, and neuropsychological effects. Basic emotions are perceived similarly by all, and emotion recognition is essential for communication and social cognition. The objective of this study was to investigate emotional recognition ability in adults with nonspecific chronic low back pain (NSCLBP). The capacity for emotion recognition was evaluated in adult patients with chronic low back pain over 6 months. Participants were divided into three groups: nonspecific chronic low back pain, specific chronic low back pain, and asymptomatic individuals. There were no significant differences in terms of gender, education, and medication use. Pain groups showed a higher proportion of married participants and a greater prevalence of anxiety symptoms. Depression symptoms did not significantly differ among the groups. No significant differences were found in disability and emotion recognition between the pain and pain-free groups. This study highlighted the high prevalence of psychological comorbidities in patients with chronic low back pain, regardless of the cause. It was found through the use of the Numeric Pain Rating Scale (NRS), employed to subjectively assess pain intensity, along with the Facial Emotion Recognition Test (FERT), used to assess people's ability to recognize basic facial emotions in images, that there is a correlation between these two methods in the NSCLBP group. In other words, the higher the pain intensity, the lower the accuracy of FERT performance. Therefore, emotion recognition in patients with intense chronic low back pain might impact social interaction, but further studies with larger samples are needed to confirm these results.